Sadayu for Solo Soprano Saxophone: A Creative Research in Music Composition - Sookjaeng, Attakorn (Rangsit Music Journal, 2024)
This creative research Sadayu is a new composition for solo soprano saxophone. The piece aims to create a new literature for soprano saxophone, to contribute to the academic field of music in Thailand, and to introduce a contemporary composition that integrates elements of Thai traditional music and culture. Sadayu draws inspiration from a segment of the Ramayana literature in which the large mythical bird named Sadayu obstructs Tossakan who is attempting to abduct Sita. The central concept of the piece is to demonstrate the vibrant colors of the melodic line through the use of contemporary techniques including alternate fingering, bisbigliando, a wide vibrato spanning a quarter of a tone, and rapid passages that incorporate swift changes in pitch collection. Additionally, the composition incorporates techniques from Thai traditional music in its melody, specifically Sabad and Uean. The piece has been successfully accomplished by having been performed internationally and is published by Emerald Music Publications.